Pelatihan Membuat Proposal Bisnis dengan Model Bisnis Canvas - Sonjaya, Nana Supriatna; Yudianto, Agus; Nurpratama, Meddy; Firdaus, Taufansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This This training activity is important because business proposals are the main tool in business continuity, getting investors, and developing business opportunities. With the ability to prepare solid proposals and assess proposals carefully, this business proposal training can increase the chances of business success and ensure that working with the best and most appropriate proposals is in line with strategic goals. This program, through the dedication of the Wiralodra University Faculty of Economics team, helps to refine the proposal creation and assessment process, which is a key step for business growth and success. The training methodology includes an initial needs analysis of participants, practice-based learning, and post-training evaluation to assess increased understanding. The results of the training showed an increase in participants' understanding of a more organized business structure and a more targeted marketing strategy. Most participants managed to redesign their business models by focusing more on market segments and more appropriate distribution channels. This study reveals the importance of a practical approach in entrepreneurship training, especially in the application of BMC to support business development at the village level. This Business Proposal is expected to learn techniques and strategies for preparing effective business proposals and how to carefully assess incoming proposals. This program is designed to help people increase their chances of success in getting business or investment opportunities and ensure the quality of the proposals received.